Proton pump inhibitors enhance intestinal permeability via dysbiosis of gut microbiota under stressed conditions in mice - Takashima, Shingo; Tanaka, Fumio; Kawaguchi, Yunosuke; Usui, Yuki; Fujimoto, Kosuke; Nadatani, Yuji; Otani, Koji; Hosomi, Shuhei; Nagami, Yasuaki; Kamata, Noriko; Taira, Koichi; Tanigawa, Tetsuya; et al. (Neurogastroenterology and motility, 2020)
Background Intestinal permeability and psychological stress are considered the key mechanism(s) in functional dyspepsia (FD). Although proton pump inhibitors (PPIs) are commonly used for the treatment of FD, the effect of PPIs on intestinal permeability has not been elucidated. This study investigated the effect of PPI on intestinal permeability under stressed conditions. Methods C57BL/6J mice were subjected to water avoidance stress (WAS) and administered rabeprazole (40 mg/kg) or vehicle treatment (VT). We then evaluated intestinal permeability both in vivo and ex vivo using plasma fluorescein isothiocyanate‐dextran and by assessing the paracellular permeability and transepithelial electrical resistance (TEER) in an Ussing chamber, respectively. Furthermore, we evaluated the effect of PPI‐treated fecal microbiota transplant (FMT) on intestinal permeability in vivo. Microbiota profiles of donor feces were assessed by 16S rRNA gene analysis using MiSeq and QIIME2. Key Results In the WAS treatment, PPI significantly enhanced intestinal permeability in vivo compared to that in VT. Moreover, PPI significantly increased paracellular permeability and decreased TEER in the duodenum and jejunum, respectively, compared to those in VT under stressed conditions. Moreover, both vasoactive intestinal peptide (VIP) receptor antagonist and ketotifen significantly reversed the effect of PPI on intestinal permeability. Furthermore, PPI‐treated FMT significantly increased the intestinal permeability in vivo compared to that in vehicle‐treated FMT. Proton pump inhibitors treatment altered the gut microbiota composition, indicating that PPI induced dysbiosis. Conclusions and Inferences Under stressed conditions, PPI enhances intestinal permeability via dysbiosis of gut microbiota. Vasoactive intestinal peptide and mast cells are also implicated in the underlying mechanisms. Under stressed conditions such as water avoidance stress (WAS), PPI enhances intestinal permeability via dysbiosis of gut microbiota. VIP and mast cells are also implicated in the underlying mechanisms.